PENDAMPINGAN KONSELOR SEBAYA DALAM PENCEGAHAN ANEMIA REMAJA PUTRI - Riyanti Riyanti; Legawati Legawati (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2018)
Anemia is a nutritional problem in the world, especially in developing countries. The incidence of female anemia in Indonesia is still high. Young women have ten times greater risk of anemia than young men. This is because teenage girls experience menstruation every month and are in a period of growth so that requires more iron intake. Efforts made in addition to providing blood-boosting tablets also involve the participation of peers in adolescent groups to prevent anemia in adolescents further through peer counselors on the prevention of anemia in young women. Methods of community service that is with Peer Counselor Assistance On Prevention of Young Women Anemia. This activity is carried out for 3 months which is divided into 3 stages: (1) planning stage, (2) the implementation stage, (3) the evaluation stage. The results obtained an increase in the counseling service process from 27 at the first meeting to 32.33 at the third meeting